249 Primary Thyroid Squamous Cell Carcinoma With Lung Metastasis. (11th January 2018) - Ghandour, Zahraa; Daroca, Philip
Abstract: Introduction: Primary squamous cell carcinoma (SCC) of the thyroid gland is a very rare entity representing <1% of all primary carcinomas of the thyroid gland. It affects usually older patients between the fifth and sixth decade, and is usually an aggressive entity with very poor prognosis. Case Presentation and Discussion: In this report, we describe a 66-year-old female patient who presented for evaluation of a 1.5 cm right thyroid mass with worsening hoarseness and dysphagia over the course of 3 months. Fine needle aspiration of the thyroid mass was positive for carcinoma; further classification was precluded by non-definitive cytologic features and limited material for immunohistochemical stains. Total thyroidectomy and central neck dissection were subsequently performed. The right thyroid lobe showed invasive poorly differentiated squamous carcinoma, positive for PAX8 but negative for thyroglobulin and TTF1, with acantholytic component and minimal focal mucin production. The entrapped thyroid tissue within the carcinoma was positive for all of the above markers, serving as "built-in" positive controls. PAX8 is expressed in thyroid carcinomas but not in head and neck squamous carcinomas. These findings are consistent with SCC of primary thyroid origin, with minimal secretory/mucin production. Chest CT scan showed numerous bilateral pulmonary nodular opacities with core biopsy revealing invasive poorly differentiated SCC consistent with metastatic disease. Neck CT scan showed 6 cm residual tumor in the glottic and subglottic areas with soft tissue invasion of C5. Patient was scheduled for chemotherapy and radiotherapy. Primary thyroid SCC has poor response to chemotherapy and total excision is usually recommended; hence, it should be differentiated from secondary involvement of adjacent SCC or metastases from other sites. Conclusion: To the best of our knowledge, this is the first case report of primary SCC of the thyroid with lung metastasis.